A study on Fuzzy C‐means application in Austronesian language cultural and creative product colors. Issue 3 (13th December 2017) - Wang, Ming‐Feng
Abstract: As culture has brought unlimited possibility and business opportunities, the countries propose the cultural and creative industry to strengthen the distinctive feature of their own, to distinguish the cultural differences of every country, and to avoid assimilation of powerful countries and neighbor countries, thereby revitalize the economy of that country. In countries affected by Austronesian culture, such as Taiwan and New Zealand, the rules by the Western colonial powers caused impact of different cultural uniqueness, which led to cultural differences. It is important to figure out the way to integrate exclusive cultures into diverse cultures in order to identify the cultural features of the country, promote the country's culture to others and realize the goal of the cultural and creative industry. Therefore, the purpose of the study is to provide the application of Fuzzy C‐means on cultural and creative products for designers. Finally, through the result of the design of case, cultural and creative products developed from Taiwan and New Zealand, fulfilled the purpose that the theory has been realized in practice, and the products successfully entered the markets.